New perspectives on an old grouping: The genomic and phenotypic variability of Oxalobacter formigenes and the implications for calcium oxalate stone prevention - Chmiel, John A.; Carr, Charles; Stuivenberg, Gerrit A.; Venema, Robertson; Chanyi, Ryan M.; Al, Kait F.; Giguere, Daniel; Say, Henry; Akouris, Polycronis P.; Domínguez Romero, Sergio Ari; Kwong, Aaron; Tai, Vera; et al. (Frontiers in Microbiology, 2022)
Oxalobacter formigenes is a unique bacterium with the ability to metabolize oxalate as a primary carbon source. Most kidney stones in humans are composed of calcium and oxalate. Therefore, supplementation with an oxalate-degrading bacterium may reduce stone burden patients suffering from recurrent calcium oxalate-based urolithiasis. Strains of O. formigenes are divided into two groups: group I and group II. However, the differences between strains from each group remain unclear and elucidating these distinctions will provide a better understanding of their physiology and potential clinical applications. Here, genomes from multiple O. formigenes strains underwent whole genome sequencing followed by phylogenetic and functional analyses. Genetic differences suggest that the O. formigenes taxon should be divided into an additional three species: Oxalobacter aliformigenes sp. nov, Oxalobacter paeniformigenes sp. nov, and Oxalobacter paraformigenes sp. nov. Despite the similarities in the oxalyl-CoA gene (oxc), which is essential for oxalate degradation, these strains have multiple unique genetic features that may be potential exploited for clinical use. Further investigation into the growth of these strains in a simulated fecal environment revealed that O. aliformigenes strains are capable of thriving within the human gut microbiota. O. aliformigenes may be a better therapeutic candidate than current group I strains (retaining the name O. formigenes) which have been previously tested and shown to be ineffective as an oral supplement to mitigate stone disease. By performing genomic analyses and identifying these novel characteristics, strains of better suited Oxalobacter may be identified to mitigate calcium oxalate-based urolithiasis in the future.